Numur fi khatar - Spilsbury, Louise; Khalil, Saussan; Maroki, Mowafak; Abbas, Basel; Khalil, Ali (London : Collins, 2016)
Once, there were 100,000 tigers in the world, but now these beautiful creatures are under threat of extinction. Find out the reasons for the decrease in tiger numbers, and what we can do to change it. Children can re-cap the reasons why tigers are in danger on pages 14-15 / Amazon.
Vastuullisuus- ja julkaisutiedot englanninkielisestä esiöstä.
Keywords: tiikeri; suojelu; lastenkirjallisuus